EFEK MEDIASI KOMITMEN MULTIDIMENSIONAL PADA AKTIVITAS RELATIONSHIP MARKETING DAN RETENSI KEANGGOTAAN DALAM ORGANISASI SOSIAL - YUDI SUTARSO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2003)
The objective of this research is to examine the mediating effect of multidimensional commitment on the relationship marketing (RM) activities and membership retention in the Islamic Student Association of University Students. The RM activities consist of five constructs (core service performance, recognition for contributions, member interdependence enhancement, dissemination of organizational knowledge, and reliance on external membership requirements), organizational commitment involves three constructs (continuance, normative and affective commitment). The survey was conducted from April to October 2002 in eleven city in East Java, Central Java and Yogyakarta, with 102 commissioner president and 322 members as the respondents. Statistical method used in this research is Two-step Structural Equation Model. The findings show that the mediating effect of multidimensional commitment is partially mediated. It means the membership retention is positively, directly as well as indirectly affected by RM activities. In addition, indirect effect of RM activities on retention was mediated by normative commitment.